Disparity and Policy in Drug Crime Cases Under Articles 112 and 127 of Law No. 35 of 2009 on Narcotics (A Study of Case Decision No. 2453 K/Pid.Sus/2025) - Fadli Siregar, Ryan; Azhali Siregar, Mhd.; Ramadani , Suci (Riviera Publishing, 2026)
Narcotics crimes are extraordinary crimes that have a wide impact on society. The handling of this case involves various parties, including judges who have an important role in making fair decisions. However, in practice, there is often a disparity in judges' decisions, especially in the application of Article 112 and Article 127 of Law Number 35 of 2009 concerning Narcotics. Article 112 tends to be applied to perpetrators who are actually only abusers, thus causing injustice because the threat of punishment is much heavier than Article 127 which provides space for rehabilitation. This study examines the criminal disparity in the case of a.n Musa Siagian which shows significant differences between first-instance decisions, appeals, and cassation, including changes in the legal basis from Article 112 to Article 127 at the cassation level. The method used is a descriptive qualitative approach with an analysis of court decisions and relevant legal norms. The results of the study show that there are two tendencies in the judge's mindset: positivistic and non-positivistic. The judge of first instance and the appeal was considered not to consider the humanitarian aspect and the penal guidelines in SEMA Number 3 of 2015 Jo. SEMA Number 4 of 2010. On the contrary, the Supreme Court in its cassation decision emphasized more sociolegal approaches and substantive justice. This disparity is an important concern in the reform of the narcotics criminal justice system in Indonesia so that law enforcement is more proportionate and humane, especially for narcotics abusers.